ANALISIS PROFITABILITAS BANK SYARIAH YANG TERDAFTAR DI BURSA EFEK INDONESIA - Hikmah Dwi Astuti (Jurnal At Taajir, 2021)
This research was conducted to examine the effect of variable Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), Non-Performing Financing (NPF), and of Profitability (ROA). Profitability is used to measure the effectiveness of management based on results generated from the loan repayment and investment. The ratio is important for the bank's profitability is Return On Assets (ROA). Financial ratios that affect the ROA is the CAR, FDR, and NPF. The sampling technique used was purposive sampling with the criteria of Islamic commercial bank serving the financial statements of the period December 2009 - December2014. The analysis technique used is the classical assumption of the analysis, multiple regression analysis and hypothesis test with a level of significance of 5%. The results of the research simultaneously (test F) states that the CAR, FDR, and NPF jointly affect the profitability (ROA) of banks. While the results show that the correlation coefficient between profitability (ROA) of banks with 4 independent variables of 46,5%. And the result of research partially (t) states that the variable CAR and FDR did not have a significant positive effect on profitability (ROA) of banks. And variable NPF and significant negative effect on profitability (ROA) of banks.